VD_FINDINFO Décision / 2013 / 895 vom 3. Oktober 2013 - VD Tribunal cantonal (2013)
DÉCISION D'IRRECEVABILITÉ, SOUSTRACTION D'UNE CHOSE MOBILIÈRE, ABUS DE CONFIANCE, SOUPÇON, LEASING, PROPRIÉTÉ | 138 CP, 141 CP, 310 CPP (CH), 397 al. 2 CPP (CH)